(untitled) (SCIENCE TIME JOURNAL, 2026)
The developing world is embarking on a massive research phase in the communications sphere to expand the flow of international relations. Also, proverbs are considered a reflection of a nation’s worldview, moral values, and social norms, where justice occupies a central position. The study analyzes proverbs from different linguistic and cultural contexts to identify how justice is conceptualized, evaluated, and transmitted through figurative language. Special attention is given to semantic features, metaphorical expressions, and moral implications embedded in proverbs. The findings reveal that the concept of justice is commonly associated with honesty, fairness, social balance, and moral responsibility, serving both an educational and regulatory function in society. This research contributes to paremiology, cognitive linguistics, and cultural studies by highlighting the role of proverbs in shaping and preserving ethical concepts across cultures.